The Personnel Strategy and Successfulness of Organizations (Journal of Universal Excellence, 2026)
Research Question (RQ): Do personnel strategy have impact on effectiveness of organizations?Purpose: Demonstrating the importance of stakeholder engagement for organizational success by the EFQM 2020 Model - Employee Engagement.Method: Using a qualitative method, review and use of articles, professional and scientific literature, and analytical study of the obtained data to reach the essence and conclusions.Results: The results showed that the treatment of employees is one of the important components that separates exceptional organizations from good ones. The organization must build relationships with employees that are important for its success and that lead to setting goals of the business strategy. Organizations are aware of the impact on the employee behavior for their performance and effectiveness. Not only by attracting and selecting personnel, but also by taking care of their development and training. Not because the development of knowledge leads to the utilization of employees in terms of well-being, but also to efficiency and excellent results.Organization: Research through the analysis of articles enables organizations to gain insight see into the importance of dealing with employees for further cooperation, creating sustainable value by recognizing their perception. Good relations within the organization are also reflected externally.Society: The role of involving all stakeholders is extremely important for business as well as for the company's reputation as an attractive employer. By treating employees well and defining their involvement, an advantage over other competitors is gained.Originality: The research on the involvement of stakeholders in successful organizations demonstrates interdependence between the treatment of employees and the successfulness of the organization.Limitations/Future Research: The research was conducted only on the basis of literature and sources and by processing one of the criteria of the EFQM 2020 model. For further research, it would be necessary to analyze and compare the involvement of stakeholders of several concrete companies.
Keywords: personnel strategy; personnel planning; personnel processes; organizational efficiency; employees; organization; EFQM model